2010
DOI: 10.1002/adsc.201000429
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decarboxylative Cross‐Ketonisation of Aryl‐ and Alkylcarboxylic Acids using Magnetite Nanoparticles

Abstract: In the presence of catalytic amounts of magnetite nanopowder, mixtures of aromatic and aliphatic carboxylic acids are converted selectively into the corresponding aryl alkyl ketones. As byproducts, only carbon dioxide and water are released. This catalytic cross-ketonisation allows the regioselective acylation of aromatic systems and, thus, represents a sustainable alternative to FriedelCrafts acylations.Keywords: aryl alkyl ketones; catalysis; cross-ketonisation; decarboxylation; iron Aryl alkyl ketones are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 31 publications
(11 reference statements)
3
36
0
Order By: Relevance
“…This is the case for aromatic acids [14], pivalic acid, and other acids missing alpha protons. In some cases, enolization may be severely disfavored, such as iiiiii See Fig.…”
Section: Factors Controlling the Cross-selectivitymentioning
confidence: 92%
See 1 more Smart Citation
“…This is the case for aromatic acids [14], pivalic acid, and other acids missing alpha protons. In some cases, enolization may be severely disfavored, such as iiiiii See Fig.…”
Section: Factors Controlling the Cross-selectivitymentioning
confidence: 92%
“…It has been rediscovered several times [8]. The literature on ketonization reactions has been extensively reviewed [9][10][11], but the discussion of the cross-selectivity was limited to just a few cases [14][15][16]. The interest to ketonization has been recently revived in connection with the bio-oil upgrading [17].…”
Section: Introductionmentioning
confidence: 97%
“…It has been observed that ketonic decarboxylation takes place over a wide range of metal oxide catalysts (such as MgO, BaO, CeO 2 , ZrO 2 , or TiO 2 , and mixtures thereof among others), [13,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] although a preferred catalyst cannot be identified. Therefore, it is of paramount interest for the further development of biomass transformations to optimize the catalytic process for the conversion of acids into ketones and to select the most suitable metal oxide catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, nucleophilic methylenes, Friedel‐Crafts reaction, nucleophilic acids and electrophilic acids have been used in total synthesis of (−)‐pauciflorol F, moxaverine, (−)‐6‐O‐desmethylantofine and (+)‐6‐O‐desmethylantofine, derivate of salvianolic acid B, communesin F and perophoramidine, (+)‐O‐methylthalibrine, sparstolonin B, lennoxamine, chilenine, fumaridine, 8‐Oxypseudoplamatine, 2‐O‐methyloxyfagaronine, (S)‐equol, xiamenmycin A and (±)‐glabridin . However, challenges still existed: (1) C−N and C−X (X=F, Cl, Br, I) bond may be constructed simultaneously during one procedure by the aid of decarboxylation and formation of radicals; (2) Decarboxylative cross coupling or tandem applications with boron reagent, diazonium salt, 1,3‐dicarbonyls were anticipated; (3) The ketones from reactions of arylacetic acids with aryl acids may function as useful intermediates in tandem reactions and show their significances in construction of diverse heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…The Gooßen group described a decarboxylative cross‐ketonisation 12.1 of aryl acids by employing magnetite nanoparticles (17–28 nm) as the catalyst (Eq. 12‐1).…”
Section: Decarboxylationmentioning
confidence: 99%